Kontradmirał Wacław Kłoczkowski (1873-1930) (Kronika Bydgoska, 2012)
The ‘Bydgoszcz Chronicie’ has already presented articles reminding about generals of the Polish Army (WP), who commanded the 15,h Infantry Division (15. DP) in the inter-war period in Bydgoszcz (Albin Jasiński, Władysław Jung, Wiktor Thommee, Jan Chmurowicz), or were acting commanders of the Divisional Infantry of 15. DP (Tadeusz Gałecki). This group included also commodore admirał Wacław Kłoczkowski (1873-1930). He was bom in St. Petersburg and when he completed law studies (Demydivka Law School in Jarosław with higher education school rights) he volunteered himself for the Russian navy. Soon, he took part in the Russian-Japanese war (among others in the battle of Tsushima Island - 1905) and in World War One (commander of submarines). He commanded many vessels on the Baltic and the Black Seas. In the Polish Army from March 3, 1919, he was, among others: deputy head of the Department forNavał Matters, member of the Polish Delegation in Paris, military and naval plenipotentiary of the Polish Legation in London, and second deputy head of the Army Administration. After completing the First Course Military Higher Studies Centre, unexpectedly to himself and others he became the commander of the Divisional Infantry of 15. DP in Bydgoszcz (from March 7, 1927 to September 30, 1927). It was the last assignment of commodore admirał Kłoczkowski. He died in Warsaw on January 30, 1930.